2017
DOI: 10.1002/2016jc012316
|View full text |Cite
|
Sign up to set email alerts
|

Erosion and Accretion on a Mudflat: The Importance of Very Shallow‐Water Effects

Abstract: Understanding erosion and accretion dynamics during an entire tidal cycle is important for assessing their impacts on the habitats of biological communities and the long‐term morphological evolution of intertidal mudflats. However, previous studies often omitted erosion and accretion during very shallow‐water stages (VSWS, water depths < 0.20 m). It is during these VSWS that bottom friction becomes relatively strong and thus erosion and accretion dynamics are likely to differ from those during deeper flows. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 100 publications
(134 reference statements)
1
26
0
Order By: Relevance
“…Several and accurate analyses, carried out with the aim of reproducing the morphological evolution of the Lagoon of Marano and Grado over an annual average period [44], have shown that only wind speeds exceeding 6 m/s involve the main morphodynamic changes, being quite frequent and strong enough to resuspend sediments. Moreover, these values agree with those assumed by different studies performed on the distribution of wave bottom shear stress inside Venice Lagoon [13,22,27,45] and those reproduced in many numerical applications to investigate tidal flats response to waves and tides [12,19,46,47].…”
Section: Numerical Simulation Setupsupporting
confidence: 88%
See 1 more Smart Citation
“…Several and accurate analyses, carried out with the aim of reproducing the morphological evolution of the Lagoon of Marano and Grado over an annual average period [44], have shown that only wind speeds exceeding 6 m/s involve the main morphodynamic changes, being quite frequent and strong enough to resuspend sediments. Moreover, these values agree with those assumed by different studies performed on the distribution of wave bottom shear stress inside Venice Lagoon [13,22,27,45] and those reproduced in many numerical applications to investigate tidal flats response to waves and tides [12,19,46,47].…”
Section: Numerical Simulation Setupsupporting
confidence: 88%
“…If the wind is strong enough, which means speed of at least 12 m/s, fw is The friction factor entering in Equation (13) has been computed by adopting the Soulsby formulation as given by Equation (4). This is an extensive choice taken by many authors [13,22,27,[45][46][47] and it presupposes that a rough turbulent motion is realized near the bed. Only for a few cases f w is assumed constant [21] and equal to a calibrated parameter.…”
Section: Analysis Of the Bed Shear Stressesmentioning
confidence: 99%
“…This is new; previous studies have focused on currents as the main cause for tussock formation (Bouma et al, , ; van Wesenbeeck et al, ). Waves are shallow in marsh areas, typically <0.5 m as in this study; yet they create erosional shear stresses on the seabed that match or exceed those of currents (Shi et al, , ). For currents, dense vegetation diverts forcing around patches, causing acceleration of hydrological energy at the patch perimeter, which increases shear stress to form erosion gullies (Bouma et al, , ; van Wesenbeeck et al, ).…”
Section: Discussionmentioning
confidence: 86%
“…Here, we had a natural situation with both waves and currents, where only wave forcing differed between the three exposure sites, suggesting that wave–current interactions generated the observed differences in tussocks and gully formation between sites. The physics behind wave–current interactions on erosion processes are complex and not well understood (Maza et al, ; Shi et al, , ; Yang & Irish, ). We propose a few simple principles that might explain the observed wave‐current induced sediment patterns around the vegetation patches (Figure ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation